Cochrane Corner: How Accurate are Prehospital Stroke Scales at Identifying People with Stroke or Transient Ischemic Attack? (International Journal of First Aid Education)
This is the second Cochrane Corner of Cochrane First Aid in the International Journal of First Aid Education. Like any Cochrane Corner, it summarizes the findings of a Cochrane systematic review. It is meant to give first aid trainers, laypeople providing first aid, and guideline developers direct access to highly relevant first aid-related evidence tailored to them, which they might otherwise not have access to. Additionally, this Cochrane Corner is accompanied by a visual abstract that highlights the key findings. This Cochrane Corner is based on a review that investigated the accuracy of stroke recognition scales when applied in the prehospital or emergency room setting to adults with suspected stroke. The review was developed by the Cochrane Stroke Group and is published in the Cochrane Database of Systematic Reviews 2019, Issue 4, DOI: 10.1002/14651858.CD011427.pub2. (see www.cochranelibrary.com for information). As Cochrane Reviews are regularly updated as new evidence emerges and in response to feedback, the Cochrane Database of Systematic Reviews should be consulted for the most recent version of the review. Both the Cochrane Corner and the visual abstract were reviewed by Dr. Greg Walker, the corresponding author of this Cochrane review.